2020
DOI: 10.1002/pssb.201900523
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Morphologies of Faceted GaN under the Metalorganic Vapor‐Phase Epitaxy Condition: Wulff Construction Using Absolute Surface Energies

Abstract: An equilibrium Wulff construction using absolute surface energies for various orientations is conducted to elucidate the morphology change of GaN under the metalorganic vapor‐phase epitaxy (MOVPE) condition. The calculated equilibrium shapes suggest that the morphology mainly consists of {11¯01} and {11¯00} facets under Ga‐rich condition for selective area growth (SAG) on [ 11¯00 ] lateral direction. In contrast, an equilibrium crystal shape including the larger area of {11¯01} facets and (0001) plateau with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…Pyramid consisting of { } planes at the top was predicted as an equilibrium crystal shape using first principles and ab‐initio approach. [ 24 , 33 ] The theoretical prediction that the Ga‐terminated surface has the lowest energy under Ga‐rich conditions, which is also in good agreement with our results. Thus, we believe that the triangular shape is actually a hexagonal pyramid composed of six of planes and one (000 ) plane as a base in the 3D space.…”
Section: Resultssupporting
confidence: 91%
“…Pyramid consisting of { } planes at the top was predicted as an equilibrium crystal shape using first principles and ab‐initio approach. [ 24 , 33 ] The theoretical prediction that the Ga‐terminated surface has the lowest energy under Ga‐rich conditions, which is also in good agreement with our results. Thus, we believe that the triangular shape is actually a hexagonal pyramid composed of six of planes and one (000 ) plane as a base in the 3D space.…”
Section: Resultssupporting
confidence: 91%
“…The enhanced LOG of {10-11} facets for micropillars with planar pillar tops (cf section 3.1) indicates that the (0001) top facet will be maintained even for larger growth times. Combined with recent calculations of absolute surface energies during GaN SAG under MOVPE growth conditions [38], our observations suggest the pillar morphology of samples B, C 1 , and H, consisting of {10-11} facets and a (0001) top facet, to largely represent the equilibrium morphology under N-rich conditions and high T SAG . Every pit corresponds to a threading dislocation termination.…”
Section: Variation Of Growth Time (F G H)supporting
confidence: 79%
“…In our previous studies, we have theoretically predicted the equilibrium crystal shapes based on Wulff plot using absolute surface energies for the SAG on nonpolar lateral direction. 24) Although the constructed equilibrium shapes are qualitatively consistent with the experimental results, it is difficult to theoretically predict the aspect ratio which can be compared with experiments. In order to exactly compare the calculated results with experiments, the effect of growth kinetics on GaN non-planar facets should be taken into account.…”
mentioning
confidence: 61%
“…This conclusion coincides with the experiment that exhibits a wide area of 0001 ( ) plateau during SAG by MOVPE using N 2 carrier gas, 9) which cannot be achieved from the analysis of equilibrium crystal shape for the SAG. 24) In summary, we have investigated the behavior of Ga adatom on GaN non-planar facets during MOVPE on the basis of ab initio calculations. For non-planar facet consisting of 1100 ( ) and 1101 ( )planes, we have found that the migration from nonplanar facet to planar 1100 ( )and 1101 ( )surfaces hardly occurs regardless of carrier gas.…”
mentioning
confidence: 99%